Study of the Rheological Properties of PVC Composites Plasticized with Butoxyethyl Adipates - Irina N. Vikhareva; Guliya K. Aminova; Aliya K. Mazitova (ChemEngineering, 2021)
Polyvinyl chloride compositions are widely used to obtain various types of products. In the composition of the PVC composite, one of the main ingredients is a plasticizer, the introduction of which makes it possible to vary the characteristics of the obtained polymeric materials and products and significantly expand the range of their application. Manufacturability in the processing of polyvinyl chloride compositions serves as an important criterion for the suitability and economic efficiency of the developed plasticizer. In the modern world, the high quality of products is directly related to their environmental safety. In this regard, the work describes the production of environmentally friendly plasticizers based on adipic acid and ethoxylated butanol. Their physicochemical indicators have been investigated. The effect of the obtained additives on the rheology of PVC composites has been studied. The values of the flow characteristics of the melts of the developed PVC compositions plasticized with butyl butoxyethyl adipate and decyl butoxyethyl adipate were estimated. It was shown that the fluidity of melts, in comparison with compounds of a similar composition containing industrial dioctyl phthalate, is characterized by even slightly higher values.